Analysis of the efficacy of subclinical doses of esketamine in combination with propofol in non-intubated general anesthesia procedures - a systematic review and meta-analysis - Haoming Chen; Xizhi Ding; Guilin Xiang; Liu Xu; Qian Liu; Qiang Fu; Peng Li (BMC Anesthesiology, 2023)
Abstract Background The number of non-intubated general anesthesia outside the operating room is growing as the increasing demand for comfort treatment. Non-intubated general anesthesia outside the operating room requires rapid onset of anesthesia, smoothness, quick recovery, and few postoperative complications. Traditional anesthetic regimens (propofol alone or propofol and opioids/dezocine/midazolam, etc.) have severe respiratory and circulatory depression and many systemic adverse effects. In this paper, we compare the effectiveness and safety of propofol and subclinical doses of esketamine with other traditional regimens applied to non-intubated general anesthesia through a systematic review and meta-analysis. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, VIP, and Sinomed databases for the period from January 2000 to October 2022. We rigorously screened the literature according to predefined inclusion and exclusion criteria, while risk assessment of the studies was performed using The Cochrane Collaboration’s tool, and statistical analysis of the data was performed using RevMan 5.4 software. The main outcome indicators we evaluated were the various hemodynamic parameters and incidence of various adverse effects between the experimental and control groups after induction of anesthesia. Results After a rigorous screening process, a total of 14 papers were included in the final meta-analysis. After risk bias assessment, three of the papers were judged as low risk and the others were judged as having moderate to high risk. Forest plots were drawn for a total of 16 indicators. Meta-analysis showed statistically significant differences in HR’ WMD 3.27 (0.66, 5.87), MAP’ WMD 9.68 (6.13, 13.24), SBP’ WMD 5.42 (2.11, 8.73), DBP’ WMD 4.02 (1.15, 6.88), propofol dose’ SMD -1.39 (-2.45, -0.33), hypotension’ RR 0.30 (0.20, 0.45), bradycardia’ RR 0.33 (0.14, 0.77), hypoxemia or apnea’ RR 0.45 (0.23, 0.89), injection pain’ RR 0.28 (0.13, 0.60), intraoperative choking’ RR 0.62 (0.50, 0.77), intraoperative body movements’ RR 0.48 (0.29, 0.81) and overall incidence of adverse reactions’ RR 0.52 (0.39, 0.70).The indicators that were not statistically different were time to wake up’ WMD − 0.55 (-1.29, 0.19), nausea and vomiting 0.84’ RR (0.43, 1.67), headache and dizziness’ RR 1.57 (0.98, 2.50) and neuropsychiatric reaction’ RR 1.05 (0.28, 3.93). The funnel plot showed that the vast majority of studies fell within the funnel interval, but the symmetry was relatively poor. Conclusion In non-intubated general anesthesia, the combination of subclinical doses of esketamine and propofol did reduce circulatory and respiratory depression, injection pain, and other adverse effects, while the incidence of esketamine’s own side effects such as neuropsychiatric reactions did not increase, and the combination of the two did not cause the occurrence of new and more serious adverse reactions, and the combination of the two was safe and effective. Trial registration PROSPREO registration number: CRD 42022368966.